Hereditary Diffuse Gastric Cancer: Multidisciplinary Case Report with Review of the Literature. (6th February 2011) - Wilcox, Rebecca; Perpich, Melody; Noffsinger, Amy; Posner, Mitchell C.; Cooper, Kumarasen
Abstract : Hereditary diffuse gastric cancer (HDGC) is a rare, inherited cancer syndrome with at least one fourth of HDGC patients having an autosomal dominantly inherited mutation of CDH1 ( E-Cadherin ). Penetrance is relatively high (70–80% lifetime risk for gastric cancer). It is important for pathologists to recognize the syndrome's phenotype in early gastric lesions: patchy intramucosal signet ring cells often associated with pagetoid spread. Due to the insidious nature of this lesion, surveillance is limited and currently prophylactic gastrectomy is an option chosen by many HDGC patients. We present a case report from a multidisciplinary team of authors with a review of the literature that includes the updated guidelines for CDH1 genetic testing.